Carbonized steel slag aggregate ultra-high performance concrete and preparation method thereof

By carbonizing the steel slag and using it in ultra-high performance concrete, the problem of cracking caused by expansion of steel slag aggregate during hydration reaction is solved, and the stability of the material is improved and the amount of river sand is reduced, while promoting the Recycling of steel slag.

CN119461995APending Publication Date: 2025-02-18ZHONGSHAN ADVANCED ENG & TECH RES INST WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410607526.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete has poor volume stability when using steel slag aggregate, which causes the material to expand during hydration reaction and crack.

Method used

By carbonizing the steel slag, free calcium oxide is converted into dense calcium carbonate, thereby reducing the expansion risk of steel slag aggregate, and using carbonized steel slag aggregate to replace some river sand to optimize material combinations.

Benefits of technology

It effectively improves the stability of steel slag aggregate, reduces the amount of river sand, improves the mechanical properties of concrete, and realizes the recycling of steel slag, reducing production costs and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461995A_ABST
    Figure CN119461995A_ABST
Patent Text Reader

Abstract

The invention relates to carbonized steel slag aggregate-based ultra-high performance concrete and a preparation method thereof. The invention provides carbonized steel slag aggregate-based ultra-high performance concrete. The carbonized steel slag aggregate-based ultra-high performance concrete comprises the following raw materials by mass: 722kg / m < 3 > of cement, 168kg / m < 3 > of silica fume, 103kg / m < 3 > of stone powder, 556kg / m < 3 > of river sand with four-grade particle size, 631kg / m < 3 > of carbonized steel slag with four-grade particle size, 177kg / m < 3 > of water and 18kg / m < 3 > of a water reducing agent. The carbonized steel slag aggregate is adopted to replace part of river sand, the adding amount of the river sand can be reduced on the basis of guaranteeing the mechanical strength and avoiding cracking, and meanwhile the industrial solid waste steel slag is effectively utilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a carbonized steel slag aggregate-based ultra-high performance concrete and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete (UHPC) is a new type of cement-based material with high strength, high durability and high toughness. It has broad application prospects in special projects such as high-rise buildings, marine engineering buildings, road and bridge construction. However, UHPC has strict requirements on raw materials and uses a high proportion (>40%) of natural high-quality river sand, resulting in higher carbon emissions and higher material costs. Therefore, in order to reduce the use of natural high-quality river sand in UHPC and find alternatives to river sand, a variety of solid wastes are added to the UHPC system to achieve ecological development.

[0003] At the same time, my country's industry is developing rapidly and the amount of solid waste generated is huge. The annual production of solid waste exceeds 10 billion tons, and the accumulated industrial solid waste over the years exceeds 60 billion tons. With the continuous improvement of the economic level, the amount of solid waste generated in my country will continue to grow. The huge amount of solid waste has caused problems such as environmental pollution, land occupation and resource waste. The dumping of solid waste has caused environmental pollution and damage; the problems caused by the disposal of industrial waste have become more and more serious, and even endanger human health. Steel slag is the main waste slag produced in the industrial steelmaking process. It is a relatively representative type of solid waste material. The steel slag produced by domestic steel enterprises cannot be processed in time, resulting in a large amount of steel slag occupying land and polluting the environment. However, steel slag is not irreusable: steel slag contains usable components such as calcium oxide, iron, and magnesium oxide. The main domestic treatment processes are: hot pouring method, wind quenching method, drum method, granulation wheel method, hot stuffy method, etc. Through the above method, steel slag can be recycled. In addition to being used for railway gravel, road pouring, agricultural fertilizer production, sintering ore, producing steel slag bricks and cement, steel slag can also be used as metallurgical raw materials, recycling scrap steel, as sintering materials, as blast furnace flux, and as steelmaking return slag; in road engineering, steel slag can be used to produce cement and concrete admixtures, replacing crushed stone and fine aggregate; steel slag is used in new building materials engineering to prepare new concrete and carbonized steel slag building materials; steel slag is also used to prepare unfired bricks, foundry sand, cement expansion agent, fluidized sand hardener, etc. At the same time, microcrystalline glass prepared from steel slag has been mass-produced in many countries since its advent in the 1960s; in environmental engineering, the higher alkalinity and larger specific surface area of ​​steel slag can be used to treat wastewater.

[0004] In recent years, my country has used steel slag as concrete aggregate in building materials and has made some use of it. However, there are great hidden dangers in the volume stability of steel slag. The volume expansion of calcium hydroxide (Ca(OH)2) generated by the later hydration reaction of free calcium oxide (f-CaO) in steel slag is the main reason for the poor volume stability of steel slag cementitious materials. How to safely incorporate steel slag into the concrete system has become an urgent problem to be solved. Summary of the invention

[0005] In order to solve the problems existing in the existing technology, this paper uses carbonized steel slag of different particle sizes to replace river sand to prepare ultra-high performance concrete. On the one hand, it effectively utilizes the harmful by-product of steel industry production, steel slag, eliminates the safety risks of using steel slag aggregate in UHPC, and realizes the recycling of solid waste; on the other hand, it prepares ultra-high performance concrete with low river sand usage, while reducing the production cost and carbon emissions of UHPC, providing technical support for the large-scale production and preparation of UHPC. The specific contents are as follows:

[0006] 1. Steel slag is crushed and screened to obtain different particle sizes. After carbonization treatment, the free calcium oxide on the surface of the steel slag is converted into dense calcium carbonate (CaCO3), which coats the steel slag aggregate, thereby reducing the risk of concrete cracking caused by its expansion;

[0007] 2. Propose an optimization design system for ultra-high performance concrete materials based on carbonized steel slag aggregate, study the effect of the volumetric dosage of carbonized steel slag on the fluidity, flexural strength and compressive strength of UHPC, determine the optimal amount of carbonized steel slag to replace river sand, and form related new material products.

[0008] The carbonized steel slag aggregate ultra-high performance concrete of the present invention comprises the following raw material components: silicate cement, stone powder, silica fume, first-grade sand of 0.6-1.25 mm, second-grade sand of 1.25-2.36 mm, third-grade sand of 2.36-4.75 mm, fourth-grade sand of 4.75-8 mm, carbonized steel slag with fourth-grade particle sizes of 0.6-1.25 mm (CSSA1), 1.25-2.36 mm (CSSA2), 2.36-4.75 mm (CSSA3), 4.75-10.55 mm (CSSA4), polycarboxylate water reducer, and water.

[0009] The specific preparation method of carbonized steel slag aggregate comprises the following steps:

[0010] (1) The steel slag is crushed by a crusher and then sieved to obtain steel slag of 0.6-1.25 mm, 1.25-2.36 mm, 2.36-4.75 mm, and 4.75-10.55 mm;

[0011] (2) The steel slag is placed in a carbonization tank, water is added to moisten the steel slag, and the sealed carbonization tank is filled with CO2 gas, and the pressure in the tank is maintained at 0.2 MPa for 24 hours to complete the carbonization reaction;

[0012] (3) Take out the slag and dry it in a vacuum drying oven at 40°C for 24 hours.

[0013] A carbonized steel slag aggregate ultra-high performance concrete and a preparation method thereof, comprising the following steps:

[0014] (1) Weigh the required raw materials such as Portland cement, silica fume, stone powder, river sand, carbonized steel slag aggregate, polycarboxylic acid high-efficiency water reducer and water;

[0015] (2) Pour all the raw materials into a stirring pot, stir at 140 r / min for 1 min, then add the water reducer and water, continue to stir slowly, and turn on the automatic stirring program after slurry is formed, and then stop stirring after 4 min;

[0016] (3) Pour the stirred slurry into a mold, vibrate it on a vibration table, then scrape it flat with a ruler, coat the surface with a film, and place it under laboratory conditions for 24 hours before demolding;

[0017] (4) After demolding, the test blocks are placed in a standard curing room for curing to various ages. The temperature in the curing room is 20±2℃ and the relative humidity is not less than 95%.

[0018] Beneficial Effects of the Invention

[0019] Compared with the prior art, the advantages of the present invention are:

[0020] The present invention adopts carbonized steel slag aggregate to replace part of river sand, which can reduce the amount of river sand added on the basis of ensuring mechanical strength and avoiding cracking, and effectively utilizes steel slag. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the XRD test result of steel slag aggregate;

[0022] Figure 2 It is the XRD test result of carbonized steel slag aggregate;

[0023] Figure 3 is the obtained nanoindentation image of ultra-high performance concrete;

[0024] Figure 4 These are the test results of the elastic modulus of the interface transition zone between carbonized steel slag aggregate ultra-high performance concrete and the matrix. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.

[0026] The carbonized steel slag-based ultra-high performance concrete of the present invention comprises the following raw material components: silicate cement, stone powder, silica fume, first-grade sand, second-grade sand, third-grade sand, fourth-grade sand, polycarboxylate water reducer, water and fourth-grade carbonized steel slag. The specific formula is shown in Table 1:

[0027] Table 1 Mix design

[0028]

[0029] The present invention is further described in detail below in conjunction with specific embodiments:

[0030] (1) Compressive strength test: According to the "Test method for strength of cement mortar (ISO method)" (GB / T17671-1999), 40 mm × 40 mm × 160 mm specimens were prepared, and after demolding, standard curing was performed to various ages, and their strength was tested;

[0031] (2) Nanoindentation test The TI-980 nanoindenter developed by Bruker-Hysitron was used to test and analyze the samples prepared from the test blocks cured for 28 days. Before the test, the test blocks were cut into small pieces of 20mm×20mm×20mm using a cutting machine, placed in a vacuum drying oven and dried for 12 hours, and then the surface to be observed was glued to a soft mold with a diameter of 25mm using double-sided tape, and then filled with a 1:2 mixed epoxy resin AB glue. The table was tapped lightly in the vertical direction by hand to remove as many bubbles as possible from the epoxy resin by oscillation. After standing for 12 hours and the epoxy resin was cured, the sample was demolded to obtain the test sample; the nanoindenter and the sample were as follows; Figure 2 As shown. The sample was taken and the surface to be tested was polished on sandpaper of 120 mesh, 180 mesh, 240 mesh, 400 mesh, 600 mesh, 1200 mesh, 2000 mesh, 2500 mesh and 5000 mesh respectively. At the same time, the particles and powder attached to the surface of the sample during the polishing process were cleaned with anhydrous ethanol, and the upper and lower surfaces of the test sample were polished with polishing paste, and finally the nanoindentation test was carried out. The test used the Tribolndenter nanoindenter produced by BrukerNano, USA. By controlling the load, the indenter was continuously increased to 2mN at a rate of 4mN / s, maintained for 0.2s, and then the load was unloaded. According to the above method, 7×15 points were punched at the junction of the aggregate and the matrix, with an interval of 4μm.

[0032] (3) Slag X-ray diffraction (XRD) analysis

[0033] The crushed steel slag aggregate was tested using an Empyrean model X-ray diffractometer. Before the test, a certain amount of steel slag particles was weighed and dried in a vacuum drying oven at 40°C for 12 hours, and then a certain sample was taken for testing. The X-ray diffraction analysis results are as follows Figure 1 As shown, the main components of the steel slag material are larnite, srebrodolskite, dicalcium silicate (C2S) and tricalcium silicate (C3S).

[0034] (4) X-ray diffraction analysis of carbonized steel slag

[0035] The carbonized steel slag aggregate was dried in a vacuum drying oven at 60°C for 12 h, and then XRD analysis was performed. The results were compared with those before carbonization. Figure 2 As shown, by comparison, an obvious CaCO3 diffraction peak appeared after carbonization, and the diffraction peak intensity was very high, indicating that CaCO3 was generated by carbonization. The stability of steel slag aggregate can be effectively improved by CaCO3 encapsulation.

[0036] The test results of fluidity, compressive strength and flexural strength are shown in Table 2 below. Without adding steel fiber, the compressive strength exceeds 130 MPa, the flexural strength exceeds 28 MPa, and the fluidity reaches 347.5 mm, indicating that the carbonized steel slag aggregate-based ultra-high performance concrete under this mix ratio has excellent mechanical properties.

[0037] Table 2 Mix ratio test results

[0038]

[0039] The nanoindentation test results are as follows Figure 3 and Figure 4 As shown, the test position is as follows Figure 3 As shown, the left part of the figure is the UHPC matrix, and the right part is the carbonized steel slag particles.

[0040] Figure 4 The relationship between the elastic modulus of the interface transition zone between the carbonized steel slag aggregate and the ultra-high performance concrete matrix in the carbonized steel slag aggregate ultra-high performance concrete is shown. The range of the horizontal axis 28-56μm in the figure is the observed area, among which the elastic modulus in the area between 32-44μm is significantly lower than the elastic modulus on both sides. It can be judged that this area is the interface transition zone of the carbonized steel slag aggregate UHPC; the thickness of the interface transition zone of the UHPC of the basic mix ratio is about 20μm, while the thickness of the interface transition zone of the carbonized steel slag aggregate UHPC is about 12μm, indicating that the carbonized steel slag aggregate is more closely combined with the UHPC matrix, thereby improving the mechanical properties.

[0041] In summary, carbonized steel slag is used to replace river sand to prepare ultra-high performance concrete. On the one hand, it effectively utilizes the harmful by-product steel slag produced by the steel industry, eliminates the safety hazards of using steel slag, and realizes the recycling of solid waste; on the other hand, it prepares ultra-high performance concrete with low river sand usage, while reducing the production cost of UHPC, providing technical support for the large-scale production and preparation of UHPC.

[0042] The above is only a preferred specific implementation of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A carbonized steel slag aggregate ultra-high performance concrete, characterized in that: Includes the following components: cement 722kg / m 3 , stone powder 103kg / m 3 、Silica fume 168kg / m 3 ,Carbonized steel slag aggregate 28~584kg / m 3 、River sand 595~1083kg / m 3 , water reducing agent 18kg / m 3 and water 177kg / m 3 .

2. The carbonized steel slag aggregate ultra-high performance concrete according to claim 1, characterized in that: The cement comprises silicate cement; the particle size of the cement is 0.275-79.433 μm, the cement has high strength and fast coagulation and hardening.

3. The carbonized steel slag aggregate ultra-high performance concrete according to claim 1, characterized in that: The stone powder has a particle size of 0.363 to 13.183 μm, has high bonding strength, and can increase the nucleation effect of the hydration reaction to provide sites for crystal nuclei.

4. The carbonized steel slag aggregate ultra-high performance concrete according to claim 1, characterized in that: The silica fume has a particle size of 0.24 to 45.709 μm and has high volcanic ash activity, and can fill the pores inside the concrete, so that the active silicon dioxide can undergo a secondary reaction to compact the internal structure of the concrete.

5. The carbonized steel slag aggregate ultra-high performance concrete according to claim 1, characterized in that: The sand particles include primary sand, secondary sand, tertiary sand and quaternary sand; The particle size of the primary sand is 0.6 to 1.25 mm; The particle size of the secondary sand is 1.25-2.36 mm; The particle size of the tertiary sand is 2.36-4.75 mm; The particle size of the fourth grade sand is 4.75-8 mm.

6. The carbonized steel slag aggregate ultra-high performance concrete according to claim 1, characterized in that: The carbonized steel slag includes first, second, third and fourth grade carbonized steel slag; The particle size of the first-stage carbonized steel slag is 0.6-1.25 mm; The particle size of the second-stage carbonized steel slag is 1.25-2.36 mm; The particle size of the first-stage carbonized steel slag is 2.36-4.75 mm; The particle size of the first-stage carbonized steel slag is 4.75-10.55 mm.

7. A method for preparing the carbonized steel slag aggregate ultra-high performance concrete according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components of the ultra-high performance concrete are mixed, and then molded and cured in sequence to obtain the ultra-high performance concrete.

8. The carbonized steel slag aggregate ultra-high performance concrete according to claim 7, characterized in that: The mixing comprises: first mixing cement, lime, silica fume, carbonized steel slag aggregate and first-grade sand, second-grade sand, third-grade sand and fourth-grade sand to obtain a premix; The premix, water reducing agent and water are mixed for a second time to obtain slurry.

9. The carbonized steel slag aggregate ultra-high performance concrete according to claim 7, characterized in that: The curing temperature is 18-22° C., and the relative humidity is ≥95%.